1993
DOI: 10.3109/00016489309135834
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum a Toxin Effects on Rat Jaw Muscle Spindles

Abstract: Botulinum A toxin (Botox) is used for the treatment of many muscular dystonias. However, the relief of the sustained and abnormal postures induced by Botox administration is not fully explained. In this work the possibility was considered that Botox can produce a block not only at the alpha motor endings, but also at the gamma motor endings, consequently reducing the spindle inflow to the alpha motoneurons, which have a great role in maintaining the tonic myotatic reflex. Jaw muscle spindle discharge was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
0
15

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(196 citation statements)
references
References 13 publications
5
176
0
15
Order By: Relevance
“…Although unproven, BTX-A-induced alterations in proprioception could occur through an inhibition of acetylcholine release by the gamma-motoneurons of skeletal muscle. This could lead to a subsequent change in muscle spindle activity [ 12,231. Decreased sensitivity of muscle spindles would compromise a muscle's ability to detect and relay joint position and movement information to the central nervous system, reducing proprioceptive acuity and potentially muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Although unproven, BTX-A-induced alterations in proprioception could occur through an inhibition of acetylcholine release by the gamma-motoneurons of skeletal muscle. This could lead to a subsequent change in muscle spindle activity [ 12,231. Decreased sensitivity of muscle spindles would compromise a muscle's ability to detect and relay joint position and movement information to the central nervous system, reducing proprioceptive acuity and potentially muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] During the initial weeks after injection, muscles treated with BTX-A show some variability in the size of muscle fibers, and demonstrate intra-cellular changes consistent with denervation (i.e. central mitochondria dispersed toward the periphery).…”
Section: Action On Striated Versus Smooth Musclementioning
confidence: 99%
“…In addition to this, recent research has also suggested that Bt is active at the level multiple levels, namely sensory nerve terminals, and muscle spindles, which leads to a reduction in sensory input and fewer muscle contractions (Matak 2014;Filippi 1993;Rosales 1996;). …”
Section: How the Intervention Might Workmentioning
confidence: 99%